The Quality Changes of Rice Stored Under Vacuum Conditions - Sidik, M. (Jurnal Teknologi Pertanian, 2000)
The National Logistics Agency (BULOG) the Government institution responsible formaintaining reserve food stocks-encountered problems of quality deterioration of milledrice during storage, primarily due to insect infestation and microbial infection. Previousefforts to control these problems have included use of  fumigants and contact pesticides,however increased concern about pesticide residues and their impact on the envirornnenthas led to the search for alternative approaches, including the application of modifiedatmosphere technology. In this respect, BULOG has constructed an integrated vacuumcontainer processing plant to store rice under low oxygen conditions (less than 2%). A study was carried out to observe the effect of low oxygen on the quality of riceduring prolonged storage Rice was stored for 16 months, either inside or outside, in 18specially designed polyethylene plastic containers (1,000 kg capacity per container) withan oxygen level of less than 2%. Changes were recorded in: moisture content; number ofinsects; level of fungal and yeast infecfions. and quality parameters such as proportion yellow rice, aroma, colour, and cooking factors.  The results ' revealed that lack of oxygen had a significant impact on the mortality ofinsects, and inhibited the development of fungi and yeast. The quality of rice wasrelatively unchanged after 16 months of storage-although, as the vacuum conditionsdecreased the moisture content of tile rice, it absorbed more water  during cookingand the rice became less sticky and fluffy. Overall, the results indicated that vacuumcontainers  could be used to maintain the quality of rice during long-term storage.However, this technology should be supported with selection of initial good quality riceprior to storage, and accurate planning regarding the length of storage-recognising thatthis technology is relatively expensive.Keyword: rice, storage, and vacuum condition